Development of a School Management Information System with Linktree and Google Workspace Integration - Nikmah, Siti Wasiatun; Rasiman, Rasiman; Violinda, Qristin (FKIP - Universitas Riau, 2025)
This study aims to determine the development of a school management information system with the integration of Linktree and Google Workspace. The method used is Research and Development (R&D) with a Mixed Methods approach, combining quantitative and qualitative analysis. The development follows the ADDIE model through five stages: (1) analysis of potential and issues, (2) system design, (3) development, (4) testing, and (5) evaluation. Data was collected through observation, interviews, expert validation questionnaires (content, media, and design), as well as limited testing and field testing at experimental and control schools. The research findings indicate that this system is highly feasible, practical, and effective in supporting school administration, supervision, and communication for school principals, and has the potential to be replicated in other elementary schools.